Strategic Innovation and Performance of Public Universities in Kenya - Shisia, Adam; Sang, William; Matoke, Jeremiah; Omwario, Benson Nyamweya (European Journal of Business and Management, 2014)
The current business environment is dynamic, turbulent and unpredictable. The success of business in such environment is depended on its adaptability to respond to environmental change. Strategic innovation is a strategic tool that can be used to align the firm’s resources and capabilities with opportunities in the external environment in order to enhance survival and long term success of the organization. This study aimed at finding the relationship between strategic innovation and performance of public universities in Kenya. The specific objectives of the study were to establish the nature of strategic innovations in the universities and determine the influence of strategic innovations on the performance. The population for the study was the public universities in Kenya from which the sample was selected. The researcher adopted descriptive survey design. Data to establish the relationship was obtained with the use of structured questionnaires. Data analysis was done using multi hierarchical regression model. Mean and standard deviation were also calculated and the results presented in form of tables. The researcher obtained a 63% response rate which was deemed valid for analysis. From the analysis it was established and concluded that indeed there existed a positive relationship between strategic innovation and performance of public universities in Kenya. The study was limited to the influence of strategic innovation on the performance of public universities in Kenya. The researcher recommends that future research should focus on other analysis tools and such studies have to include other institutions that are not necessarily public universities. The implication of the findings is the need for the management to align strategic innovation strategy with the wider business strategy. They have to demonstrate their capability in understanding the customer insights and offer new and significant value if their long term success and survival is to be guaranteed. Keywords
Keywords: Strategic Innovation; Knowledge Creation; Organizational Performance; Public Universities in Kenya.